Leveraging Educational Technology to Connect Mathematics, Digital Design, and Entrepreneurship in CLC Students’ Souvenir Production - Fajriah, Noor; Kusumawati, Elli; Arifin, M. Zainul; Soraya, Selfina (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to investigate how mathematics, digital technology, and entrepreneurship are integrated through the digital printing workflow in the production of souvenir keychains by CLC students, with a particular focus on how these activities support the development of creative thinking skills. Methodology: This research employed a qualitative case study using classroom observations, semi-structured interviews, document analysis, and design file reviews. Canva (web-based design platform), Heat Gun KOVA 2000W, and shrink-film materials were used during production, supported by thematic analysis of learning artifacts and performance documentation. Main Findings: The findings show that students developed applied mathematical competencies particularly measurement, proportion, and spatial reasoning while engaging in iterative digital design using Canva. Students demonstrated significant growth in digital literacy, creativity, and product refinement, and successfully produced approximately ninety keychains, all of which were sold during an exhibition, indicating emerging entrepreneurial capability. Novelty/Originality of this study: This study offers originality by demonstrating how a low-cost digital design and fabrication workflow can bridge technological learning gaps in non-formal CLC environments. Unlike prior research conducted in well-resourced settings, this study shows how accessible tools enable learners with limited technological exposure to integrate mathematics, digital production, and entrepreneurship within an authentic, technology-enhanced learning model.